Location and Grade of Prostate Cancer Diagnosed by Transperineal Template-guided Mapping Biopsy After Negative Transrectal Ultrasound-guided Biopsy. (August 2018) - Bittner, Nathan; Merrick, Gregory; Taira, Al; Bennett, Abbey; Schattel, Amy; Butler, Wayne; Galbreath, Robert; Adamovich, Edward
Abstract : Objectives: To determine the location and grade of prostate cancer diagnosed by transperineal template-guided mapping (TTMB) after negative transrectal ultrasound-guided (TRUS) biopsy. Materials and Methods: This analysis consisted of 1118 consecutive patients who underwent TTMB from January 2005 to August 2015. Eight hundred thirty-five underwent TTMB after at least 1 negative TRUS biopsy and 283 underwent TTMB as the first biopsy procedure. The study population was divided into cohorts based on the number of prior TRUS biopsy sessions (0, 1, 2, and ≥3). No patient underwent multiparametric magnetic resonance imaging. Differences in location and cancer grade detected on TTMB were evaluated as a function of the number of prior TRUS biopsies. Results: Of the 1118 patients, 679 were diagnosed with prostate cancer. This included 208, 325, 104, and 42 patients who underwent 0, 1, 2, and ≥3 prior TRUS biopsies. The incidence of cancer detection on TTMB decreased as the number of prior TRUS biopsies increased (73.5% vs. 62.4% vs. 51.7% vs. 37.2%, P <0.001); however, it became increasingly likely that TTMB would detect anterior prostate only as the number of prior TRUS biopsies increased ( P =0.007). Moreover, the incidence of high grade cancer (Gleason score ≥7) in the anterior gland increased with the number of previous TRUS biopsies. Conclusions: TTMB detected prostate cancer in over half of the patients with one or more negative TRUS biopsies. The majority of TTMB detected cancers were Gleason score ≥7. As the number of prior TRUS biopsies increased, there was a commensurate increase in the proportion of high-grade, anterior only disease.